Antiaging Effects of Vicatia thibetica de Boiss Root Extract on Caenorhabditis elegans and Doxorubicin-Induced Premature Aging in Adult Mice. (9th August 2021) - Liu, Wenwen; Guan, Yunhui; Qiao, Sicong; Wang, Jiqun; Bao, Keting; Mao, Zhifan; Liao, Liang; Moskalev, Alexey; Jiang, Bei; Zhu, Jin; Xia, Conglong; Li, Jian; et al.
Abstract : The roots of Vicatia thibetica de Boiss are a kind of Chinese herb with homology of medicine and food. This is the first report showing the property of the extract of Vicatia thibetica de Boiss roots (HLB01) to extend the lifespan as well as promote the healthy parameters in Caenorhabditis elegans ( C. elegans ). For doxorubicin- (Doxo-) induced premature aging in adult mice, HLB01 counteracted the senescence-associated biomarkers, including P21 and γ H2AX. Interestingly, HLB01 promoted the expression of collagen in C. elegans and mammalian cell systemically, which might be one of the essential factors to exert the antiaging effects. In addition, HLB01 was also found as a scavenger of free radicals, thereby performing the antioxidant ability. Lifespan extension by HLB01 was also dependent on DAF-16 and HSF-1 via oxidative stress resistance and heat stress resistance. Taken together, overall data suggested that HLB01 could extend the lifespan and healthspan of C. elegans and resist Doxo-induced senescence in mice via promoting the expression of collagen, antioxidant potential, and stress resistance.